The integration of psychological education and moral dilemmas from a value perspective - XiaoFen Jia; WenQing Wu (BMC Psychology)
Abstract The rapid evolution of internet technologies has emphasized the importance of integrating psychological education with moral dilemmas across diverse sectors. This paper investigates the interrelationship between psychological education and moral reasoning, proposing that this integration represents a pivotal approach for fostering effective educational strategies. Leveraging deep learning models, we aim to enhance both the scientific rigor and theoretical understanding of how these two domains intersect. Initially, the paper addresses inherent value challenges within psychological and moral dilemma analyses, setting the stage for deeper exploration. Subsequently, fundamental algorithms underpinning deep learning neural networks are introduced, illustrating their potential applications in studying the integration of psychological and moral values. Various features of this integration are discussed, highlighting their contributions to elucidating and interpreting complex value issues. Moreover, optimization functions pertinent to deep learning are examined, alongside their practical implications for enhancing educational practices. An empirical study is conducted to evaluate the impact of psychological feature analysis on addressing value issues through the lens of psychological education. Utilizing advanced deep learning techniques, our experimental investigation reveals significant improvements in understanding and resolving these value issues. Key findings underscore the positive influence of incorporating psychological feature analysis into educational frameworks, particularly in contexts involving moral dilemmas. These insights pave the way for more effective, integrative approaches to education, promoting holistic development and ethical reasoning among learners.